2012
DOI: 10.1038/ni.2460
|View full text |Cite
|
Sign up to set email alerts
|

The helicase DDX41 recognizes the bacterial secondary messengers cyclic di-GMP and cyclic di-AMP to activate a type I interferon immune response

Abstract: Induction of type I interferons by the bacterial secondary messengers cyclic-di-GMP (c-di-GMP) or cyclic-di-AMP (c-di-AMP) is dependent on a signaling axis involving the STING adaptor, TBK1 kinase and IRF3 transcription factor. Here we identified the helicase DEAD box polypeptide 41 (DDX41) as a pattern recognition receptor (PRR) that sensed both c-di-GMP and c-di-AMP. DDX41 specifically and directly interacted with c-di-GMP. Knockdown of DDX41 via shRNA in murine or human cells inhibited the induction of inna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
317
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 358 publications
(342 citation statements)
references
References 36 publications
7
317
2
1
Order By: Relevance
“…DDX41, like other DEAD-box helicases, has been shown to interact with and bind to nucleic acids and ATP for activation [37]. Specifically, by its DNA binding activity, DDX41 acts as a sensor of dsDNA and bacterial-derived cyclic di-nucleotides (CDN) (c-di-AMP, c-di-GMP) [40]. It also binds directly to numerous proteins within the interferon response pathway in the cytoplasm, including Stimulator of interferon genes (STING) [41].…”
Section: Ddx41 Protein Structurementioning
confidence: 99%
See 1 more Smart Citation
“…DDX41, like other DEAD-box helicases, has been shown to interact with and bind to nucleic acids and ATP for activation [37]. Specifically, by its DNA binding activity, DDX41 acts as a sensor of dsDNA and bacterial-derived cyclic di-nucleotides (CDN) (c-di-AMP, c-di-GMP) [40]. It also binds directly to numerous proteins within the interferon response pathway in the cytoplasm, including Stimulator of interferon genes (STING) [41].…”
Section: Ddx41 Protein Structurementioning
confidence: 99%
“…2b). Some of these include bacteria [produce c-di-GMP and c-di-AMP (CDN)], and poly(dA; dT) [40], invading dsDNA viruses (e.g., adenovirus, herpes virus and papillomavirus), and nearby cells that have released dsDNA fragments by necrosis [44]. The introduction of dsDNA and CDN into the cytoplasm occurs through pathogen-specific infection mechanisms, exosomes or receptor-mediated endocytosis [56].…”
Section: Ddx41 In the Sting-interferon Pathwaymentioning
confidence: 99%
“…RIG-I 11 and melanoma differentiation-associated protein 5 (MDA5) 12 can recognize viral dsRNA and recruit the CARD containing adaptor protein MAVS (also known as IPS-1, CARDIF or VISA), leading to IRF activation and the production of type I IFN. In addition to RLRs, a group of cytosolic DNA sensors such as cyclic GMP-AMP synthase (cGAS), [13][14][15] absent in melanoma 2 (AIM2), 16,17 DDX41, 18,19 Rad50, 20,21 LRRFIP1, 22 DNA-dependent activator of IRFs (DAI), 23 as well as various RNA sensors such as IFN-induced protein with tetratricopeptide repeats 1 (IFIT1) 24 also play potent roles in inducing antiviral immune response, respectively via the adaptor protein stimulator of interferon genes (STING, also known as MITA, ERIS or MPYS) or the MAVS pathway. cGAS, which was previously thought to recognize cytoplasmic dsDNA over 40 bp in a sequence-independent manner, is recently shown to recognize unpaired guanosines flanking short (12-20 bp) dsDNA (Y-form DNA) found in human immunodeficiency virus type 1 to induce type I IFN production.…”
Section: Introductionmentioning
confidence: 99%
“…C-di-GMP also controls biofilm formation, exopolysaccaride production, toxin production and related outcomes, therefore c-di-GMP can be considered to be a second messenger in bacteria [11][12][13]. In addition, our group recently reported that c-di-GMP can stimulate the innate immune system [14] and, given the fact that c-di-GMP binds to DDX41 in the cytosol, can form a complex with STING, send the signal via the TBK1-IRF3 pathway and activate type I interferons [15,16]. Therefore the receptor for c-di-GMP is DDX41 in the cytosol is different from known adjuvants such as polyIC (toll like receptor 3 on the cell surface) and CpG oligonucleotides (toll like receptor on endosome).…”
Section: Introductionmentioning
confidence: 99%